Pyramiding of tea Dihydroflavonol reductase and Anthocyanidin reductase increases flavan-3-ols and improves protective ability under stress conditions in tobacco - Kumar, Vinay (3 Biotech, 2017)
Tea (Camellia sinensis) is one of the richest sources of flavan-3-ols, an important class of flavonoids. The expression level of gene-encoded key regulatory enzymes of flavan-3-ol/anthocyanin biosynthetic pathway, dihydroflavonol 4-reductase (DFR) and anthocyanidin reductase (ANR), has been highly correlated with the flavan-3-ol contents and antioxidant activity in tea plant. In the present study, pyramiding of CsDFR and CsANR in tobacco was achieved. However, single transgenic tobacco overexpressing either CsDFR or CsANR was documented earlier. In continuation, pyramided transgenic lines were evaluated for the possible, either same or beyond, effect on flavan-3-ol accumulation and protective ability against biotic and abiotic stresses. The pyramided transgenic lines showed early flowering and improved seed yield. The transcript levels of flavan-3-ol/anthocyanin biosynthetic pathway and related genes in pyramided transgenic lines were upregulated as compared to control tobacco plants. The accumulations of flavan-3-ols were also found to be higher in pyramided transgenic lines than control tobacco plants. In contrast, anthocyanin content was observed to be decreased in pyramided transgenic lines, while DPPH activity was higher in pyramided transgenic lines. In pyramided transgenic lines, strong protective ability against feeding by Spodoptera litura was documented. The seeds of pyramided transgenic lines were also found to have better germination rate under aluminum toxicity as compared to control tobacco plants. Interestingly, the synergistic effect of these two selected genes are not beyond from transgenic lines expressing either CsDFR and CsANR alone as published earlier in terms of flavan-3-ols accumulation. However, the unique flower color and better seed germination rate are some interestingly comparable differences that were reported in pyramided lines in relation to individual transgenic plants. In conclusion, the present results reveal an interesting dynamic between CsDFR and CsANR in modulating flavan-3-ol/anthocyanin levels and functional analysis of stacked CsDFR and CsANR transgenic tobacco lines. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13205-017-0819-1) contains supplementary material, which is available to authorized users.